Roots of a cubic function

Algebra Level 4

Let a , b , c , d , e a,b,c,d,e and f f be constant real numbers such that the roots (for x x ) in x 3 + a x 2 + b x 105 = 0 x^3 + ax^2+bx-105 = 0 are each two more than the roots (for x x ) in x 3 d x 2 + e x f = 0 x^3-dx^2 + ex - f= 0 . Determine the value of 4 d + 2 e + f 4d + 2e + f .


The answer is 97.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

4 solutions

Manuel Kahayon
Jun 26, 2016

Let ( α , β , γ ) (\alpha, \beta, \gamma) be the roots of f ( x ) = x 3 + a x 2 + b x 105 f(x) = x^3 + ax^2+bx-105 ( We let f ( x ) = x 3 + a x 2 + b x 105 f(x) = x^3 + ax^2+bx-105 ). Therefore, ( α 2 , β 2 , γ 2 ) (\alpha -2, \beta -2, \gamma -2) are the roots of x 3 d x 2 + e x f x^3-dx^2 + ex - f .

But then, ( α 2 , β 2 , γ 2 ) (\alpha -2, \beta -2, \gamma -2) are the roots of f ( x + 2 ) f(x+2) , since f ( ( α 2 ) + 2 ) = f ( α ) = 0 f((\alpha - 2)+2) = f(\alpha) = 0 .

Therefore, ( α 2 , β 2 , γ 2 ) (\alpha -2, \beta -2, \gamma -2) are the roots of f ( x + 2 ) = ( x + 2 ) 3 + a ( x + 2 ) 2 + b ( x + 2 ) 105 = x 3 + ( a + 6 ) x 2 + ( 12 + 4 a + b ) x + ( 4 a + 2 b 97 ) f(x+2) = (x+2)^3 + a(x+2)^2 + b(x+2) -105 = x^3+(a+6)x^2+(12+4a+b)x+(4a+2b-97) .

This implies that x 3 + ( a + 6 ) x 2 + ( 12 + 4 a + b ) x + ( 4 a + 2 b 97 ) = x 3 d x 2 + e x f x^3+(a+6)x^2+(12+4a+b)x+(4a+2b-97) = x^3-dx^2 + ex - f . Comparing coefficients, we get that d = a 6 d = -a-6 , e = 12 + 4 a + b e = 12+4a+b and f = 97 4 a 2 b f = 97-4a-2b .

Therefore, our required answer is 4 d + 2 e + f = 4 ( a 6 ) + 2 ( 12 + 4 a + b ) + ( 97 4 a 2 b ) = 97 + 24 24 + 8 a 8 a + 2 b 2 b = 97 4d+2e+f = 4(-a-6)+2(12+4a+b)+ (97-4a-2b) = 97+24-24+8a-8a+2b-2b = \boxed{97} .

Chamen Escalante
Jun 25, 2016

Let r, s, t be the roots of the first equation and u, v, w for the second.

105 = rst = 7 * 3 * 5
u = 7-2=5
v = 5-2 =3
w =3-2=1


f = uvw= 5 * 3 * 1=15
e = uv * vw * uw = 5*3 + 3 * 1 +1 * 5=23
d = u+ v+ w = 1+3+5= 9

4d + 2e + = 97

Typo last line, f {\color{#D61F06}{f}} +4d+2e=97.

Niranjan Khanderia - 1 year, 10 months ago

L e t p , q , r b e t h e r o o t s o f s e c o n d e q u a t i o n . p + 2 , q + 2 , r + 2 a r e t h e r o o t s o f f i r s t e q u a t i o n . f r o m V i e t a s f o r m u l a : S e c o n d e q u a t i o n : p + q + r = d , p q + q r + r p = e , p q r = f . F i r s t e q u a t i o n : ( p + 2 ) ( q + 2 ) ( r + 2 ) = 105 B u t ( p + 2 ) ( q + 2 ) ( r + 2 ) = p q r + 2 ( p q + q r + r p ) + 4 ( p + q + r ) + 8 = 105 105 = f + 2 e + 4 d + 8 = 105. S o 4 d + 2 e + f = 105 8 = 97. Let~p,~q,~r~be~the~roots~of~second~equation.\\ \therefore~p+2,~q+2,~r+2~are~the~roots~of~first~equation.\\ ~~~\\ \implies~from~ Vieta's~ formula:-\\ ~~~\\ Second~equation :-~~p+q+r=d,~~~~~pq+qr+rp=e,~~~~~pqr=f.\\ ~~~\\ First~equation :-~~\\ (p+2)(q+2)(r+2)=105~~~~~\\ But~~(p+2)(q+2)(r+2)~=~pqr~+~2(pq+qr+rp)~+~4(p+q+r)~+~8=105\\ \implies~105=~f~+~2e~+~4d~+~8~=~105.\\ So~~4d + 2e + f~=~105~-~8~=~\Large \color{#D61F06}{97}.

Hung Woei Neoh
Jul 1, 2016

Let the roots of x 3 + a x 2 + b x 105 = 0 x^3+ax^2+bx-105=0 be p , q , r p,q,r . From Vieta's formula, we have

p + q + r = a p q + p r + q r = b p q r = 105 \color{#3D99F6}{p+q+r = -a}\\ \color{#D61F06}{pq+pr+qr=b}\\ \color{#EC7300}{pqr=105}

Now, we know that the roots of x 3 d x 2 + e x f = 0 x^3-dx^2+ex-f=0 are p 2 , q 2 , r 2 p-2,q-2,r-2 . Again, from Vieta's formula, we have:

( p 2 ) + ( q 2 ) + ( r 2 ) = d p + q + r 6 = d d = a 6 (p-2)+(q-2)+(r-2)=d\\ \color{#3D99F6}{p+q+r}-6=d\\ d=\color{#3D99F6}{-a} -6

( p 2 ) ( q 2 ) + ( p 2 ) ( r 2 ) + ( q 2 ) ( r 2 ) = e p q 2 p 2 q + 4 + p r 2 p 2 r + 4 + q r 2 q 2 r + 4 = e p q + p r + q r 4 ( p + q + r ) + 12 = e e = b 4 ( a ) + 12 = b + 4 a + 12 (p-2)(q-2)+(p-2)(r-2)+(q-2)(r-2) = e\\ pq-2p-2q+4+pr-2p-2r+4+qr-2q-2r+4=e\\ \color{#D61F06}{pq+pr+qr} - 4(\color{#3D99F6}{p+q+r})+12=e\\ e=\color{#D61F06}{b} - 4(\color{#3D99F6}{-a)}+12 = b+4a+12

( p 2 ) ( q 2 ) ( r 2 ) = f ( p q 2 p 2 q + 4 ) ( r 2 ) = f p q r 2 p r 2 q r + 4 r 2 p q + 4 p + 4 q 8 = f p q r 2 ( p q + p r + q r ) + 4 ( p + q + r ) 8 = f f = 105 2 b + 4 ( a ) 8 = 97 2 b 4 a (p-2)(q-2)(r-2)=f\\ (pq-2p-2q+4)(r-2)=f\\ pqr-2pr-2qr+4r-2pq+4p+4q-8=f\\ \color{#EC7300}{pqr} - 2(\color{#D61F06}{pq+pr+qr}) + 4(\color{#3D99F6}{p+q+r})-8=f\\ f=\color{#EC7300}{105} - 2\color{#D61F06}{b} + 4(\color{#3D99F6}{-a}) -8= 97-2b-4a

4 d + 2 e + f = 4 ( a 6 ) + 2 ( b + 4 a + 12 ) + 97 2 b 4 a = 4 a 24 + 2 b + 8 a + 24 + 97 2 b 4 a = 97 4d+2e+f\\ =4(-a-6)+2(b+4a+12)+97-2b-4a\\ =-4a-24+2b+8a+24+97-2b-4a\\ =\boxed{97}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...